2017
DOI: 10.1186/s12905-017-0446-3
|View full text |Cite
|
Sign up to set email alerts
|

Effect of simvastatin on monocyte chemoattractant protein-1 expression in endometriosis patients: a randomized controlled trial

Abstract: BackgroundSimvastatin is a promising new drug for the treatment of endometriosis. It is a cholesterol-lowering drug that acts by inhibiting HMG-CoA reductase, resulting in a decrease in mevalonate, a precursor of cholesterol and monocyte chemoattractant protein-1 (MCP-1). This study investigated the effect of pre-operative oral simvastatin administration on MCP-1 gene expression and serum MCP-1 protein levels in patients with endometriosis.MethodsA prospective, randomized, controlled study was conducted at the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 33 publications
0
14
1
Order By: Relevance
“…Many investigators have proved that MCP-1 concentration is elevated in the peritoneal fluid of women with endometriosis. The serum level of MCP-1 nonetheless remains a controversial issue since half of studies show significant difference between the women with endometriosis and the control groups and the rest studies do not [24,25]. In our study, no statistically significant difference was found between the two groups.…”
Section: Discussioncontrasting
confidence: 70%
“…Many investigators have proved that MCP-1 concentration is elevated in the peritoneal fluid of women with endometriosis. The serum level of MCP-1 nonetheless remains a controversial issue since half of studies show significant difference between the women with endometriosis and the control groups and the rest studies do not [24,25]. In our study, no statistically significant difference was found between the two groups.…”
Section: Discussioncontrasting
confidence: 70%
“…VEGF and sflt‐1 are angiogenic factors and receptors that can increase vascular permeability, effectively promote the proliferation of endometrial stromal cells in patients, thus, leading to the occurrence and progression of the disease 38 . MCP‐1 is mainly secreted by stromal cells and tumor cells, which can promote the expression of VEGF and induce endothelial cell migration 39 . Both TNF‐α and IL‐6 can take part in the inflammatory response and immune injury process of the body, as well as also have the role of regulating certain angiogenic factors, thus, inducing and promoting endometriosis 40 .…”
Section: Discussionmentioning
confidence: 99%
“…This review discusses the following: endometriosis is constantly exposed to environmental stressors, such as superoxide anions; superoxide is one of important mediators in persistent pain [7,14,27,43,60,75,87,89,104]; and some compounds and natural substances that suppress the pain caused by superoxide may be potential candidates for nonhormonal therapy for endometriosis [82,84,85,[91][92][93][94][95][96][97][98][99][100][101][102][103]. First, we summarize the mechanism by which superoxide anion is produced in large amounts in endometriosis and thus contributes to pain (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Simvastatin, a HMG-CoA Reductase Inhibitor Simvastatin (20 mg daily for 4 months) significantly reduced dyspareunia, dysmenorrhea, and pelvic pain scores 6 months after DOI: 10.1159/000512628 laparoscopic surgery as assessed by visual analog scale (VAS) scores [102]. However, treatment with 20 mg/day of simvastatin for 2 weeks did not reduce the expression of either the chemokine MCP-1 gene or macrophage-specific genes, suggesting that simvastatin is not ideal for treating endometriosis [103]. No clinical studies have evaluated the efficacy of simvastatin as a first-line treatment for patients with endometriosis before surgery.…”
Section: A Brief Description Of 4 Drugs Belonging To Group 3 (Clinical Trials)mentioning
confidence: 99%